Associação de Modificação do Comportamento: contingencies for Behavior Analysis institutionalization in Brazil - Torres, Jaqueline de Andrade; Cândido, Gabriel Vieira; Miranda, Rodrigo Lopes (Perspectivas em Análise do Comportamento, 2020)
Studies in History of Behavior Analysis, in Brazil, have been debated with focus especially on the initial years of its scientific community conformation. This research aimed to present the Associação de Modificação do Comportamento (AMC). Founded in 1974 and extinguished in 1984, with headquarters and operations in the state of São Paulo, AMC intended to promote behavior modification as a scientific and professional field. It gathered members, promoted events and published specialized journals. In this sense, part of those documents was the data source of this study, whose purpose was trying to know the profile of those people, that is: who they were, what they read and what they talked about. The data pointed to predominance of the feminine gender, singular writing, affiliations from the state of São Paulo, interest in educational topics and emphasis on applied area. There were also collaborations from international actors (Canada, United States and Mexico). Still, methodological limitations need to be taken into account, without, however, neglecting the fact that the results of this research provide conjectures for a more sophisticated understanding of Behavior Analysis in Brazil, as well as assisting in the preservation of its memory.